Yes, We Are Still Talking about Cylosporin vs. Infliximab in Steroid Resistant Acute Severe Ulcerative Colitis. (November 2017) - Bernstein, Charles N; Kornbluth, Asher
Abstract : Abstract: : The Spanish IBD Registry (ENEIDA) is reporting in this issue of the Journal on a retrospective assessment of outcomes of cyclosporine use and infliximab use to treat steroid refractory acute severe ulcerative colitis (SR‐ASUC) between 1989 and 2013. Overall, they found similar outcomes in terms of 3 month and 1 year colectomy rates. Serious adverse events were lower in cyclosporine users. While this study does not meet the standard of a prospective randomized controlled trial, it does remind us that cyclosporine can be effective in (SR‐ASUC) and should be considered in those who have already failed antibody to tumor necrosis factor therapy or as a bridge to immunomodulators that have a slower onset of action.